2014
DOI: 10.1021/ja412084b
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of rRNA Modifications Using Stable Isotope Labeling and Mass Spectrometry

Abstract: Post-transcriptional RNA modifications that are introduced during the multistep ribosome biogenesis process are essential for protein synthesis. The current lack of a comprehensive method for a fast quantitative analysis of rRNA modifications significantly limits our understanding of how individual modification steps are coordinated during biogenesis inside the cell. Here, an LC-MS approach has been developed and successfully applied for quantitative monitoring of 29 out of 36 modified residues in the 16S and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
122
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(126 citation statements)
references
References 41 publications
2
122
0
Order By: Relevance
“…Given that most 50S subunits in cells are associated with 30S subunits at sufficient concentrations of Mg 2+ , it is reasonable to speculate that the physiological substrate for RlmE is not the 50S subunit, but rather the 45S precursor, because Um2552 in H92 of 23S rRNA is located on the interface side of the 50S subunit (24)(25)(26). Quantitative analyses of rRNA modifications by HPLC/MS have shown that the level of Um2552 surges during late steps of 50S assembly (32,33), and these results are consistent with our observations. To obtain insights into the function of an RNA modification responsible for a specific biological process, it is necessary to determine whether the RNA-modifying enzyme or the RNA modification itself plays a pivotal role in the process.…”
Section: Discussionmentioning
confidence: 99%
“…Given that most 50S subunits in cells are associated with 30S subunits at sufficient concentrations of Mg 2+ , it is reasonable to speculate that the physiological substrate for RlmE is not the 50S subunit, but rather the 45S precursor, because Um2552 in H92 of 23S rRNA is located on the interface side of the 50S subunit (24)(25)(26). Quantitative analyses of rRNA modifications by HPLC/MS have shown that the level of Um2552 surges during late steps of 50S assembly (32,33), and these results are consistent with our observations. To obtain insights into the function of an RNA modification responsible for a specific biological process, it is necessary to determine whether the RNA-modifying enzyme or the RNA modification itself plays a pivotal role in the process.…”
Section: Discussionmentioning
confidence: 99%
“…The bulky Ψ-CMC adduct acts as a strong stop to reverse transcriptase (RT) one nucleotide 3 0 of the Ψ, allowing Ψ locations to be mapped using gene-specific primer extension assays (Bakin & Ofengand, 1993). More recently, techniques have been developed to allow site-specific identification and quantification of Ψ using thin-layer chromatography (Zhao & Yu, 2004), as well as mass spectrometry-based techniques that allow detection of normally mass silent Ψ (Durairaj & Limbach, 2008;Popova & Williamson, 2014). While powerful in some contexts, these assays are low throughput and are best suited to identification of Ψs in highly abundant RNAs.…”
Section: Detection Of Pseudouridinementioning
confidence: 99%
“…Incomplete reactions, side products, and unstable response factors prevent quantitative analysis by this approach. In consequence there is an increasing interest in derivatization-free MS/ MS-based approaches that allow quantitative analysis, 26,27 and which have recently included isotope labeling 28,29 So called hypermodified C derivatives are formed via further modification of C. At present, they comprise Cm, m 1 C, (found in all domains of life, predominantly in tRNA 1 ), m 3 C (in rRNA of Eubacteria 1 ), as well as 3-(3-amino-3-carboxypropyl)-C .axap3C/ 30,31 and m 1 acap 3 C 1 in rRNA of eukaryotes (Fig. 1).…”
Section: Physicochemical Properties Of Cmentioning
confidence: 99%